A raising operator formula for Macdonald polynomials - J. Blasiak; M. Haiman; J. Morse; A. Pun; G. H. Seelinger (Forum of Mathematics, Sigma, 2025)
We give an explicit raising operator formula for the modified Macdonald polynomials